Executive Compensation in Controversial Industries: A Qualitative Study of Pay-for-Performance Sensitivity in Sin Companies - Grace Yulianti; Dadang Irawan; Tanti Sugiharti (International Journal of Business Law, Business Ethic, Business Comunication & Green Economics, 2025)
This qualitative literature review examines the pay-for-performance sensitivity in managerial compensation within controversial industries, often referred to as "sin" companies, including sectors such as tobacco, alcohol, and gambling. The review synthesizes existing studies on executive compensation structures in these sectors, highlighting the unique challenges and ethical considerations they face due to societal scrutiny and regulatory pressures. Findings suggest that sin companies tend to offer higher compensation packages with stronger pay-for-performance sensitivity to attract and retain executives in high-risk environments. However, the alignment between executive incentives and long-term sustainability is often compromised by external social and ethical factors. Despite the growing interest in this area, limited empirical research specifically focusing on sin industries has resulted in a gap in understanding how these dynamics play out across different controversial sectors. The review calls for further research to explore these relationships in greater depth and across diverse global contexts.